Insegnare le scienze per costruire un pensiero critico e combattere l’anti-scienza - Aquilini, Eleonora (Chimica nella Scuola, 2024)
The study of science should promote openness and a critical spirit, while especially today in science teaching the trivialization of academic knowledge is increasingly evident as the educational level is lowered: specialized language is used, and the important steps that lead to understanding the problem are omitted. Science teaching is thus reduced to the reproduction of sentences that often have no meaning for the student. Dogmatism, which accompanies this way of teaching and disseminating science, is the main cause of the success of anti-scientific ideas. Schools have an important role in changing the image of science in the citizen’s perception of it. Acquiring the way of thinking, which is called scientific, also means perceiving doubt as a value and not as a destabilizing uncertainty from which to escape.